Gato con botas - Wheeler, Thomas.; Aguilar, Joe M.; Ouaou, Latifa, 1961-; Miller, Chris.; Banderas, Antonio.; Hayek, Salma, 1968-; Galifianakis, Zach.; Lynch, Brian.; Davies, William.; Toro, Guillermo del, 1964-; Adamson, Andrew.; Raimo, Michelle.; et al. (Paramount Home Entertainment, 2012)
Los acontecimientos que condujeron a la reunión de la espada del gato con Shrek y sus amigos.